Afiksasi Bahasa Dayak Ketungau Sesat - Pabianus Simon (Journal of Mandalika Literature, 2024)
This research focuses on the form of affixation of the Ketungau Sesat Dayak language. The method used in this research is descriptive. The data in this research is in the form of affixations of the Ketungau Sesat Dayak language. Based on the results of research conducted, there are four forms of affixes in the Ketungau Sesat Dayak language, consisting of prefixes, infixes, suffixes and confixes. From the data found, there were 24 affixes consisting of 13 prefixes, 2 infixes, 5 suffixes and 4 suffixes. The Ketungau Sesat Dayak language prefixes (BDKS) consist of bǝ-, tǝ-, lǝ-, ngǝ-, di-, mǝ-, ng-, ny-, kǝ, pǝ-, pǝm-, pǝngǝ-, and pǝny-. The Dayak Ketungau Sesat (BDKS) language infix consists of -em- and –el-. The Ketungau Sesat Dayak language suffixes (BDKS) consist of –ne, -mǝ, -tek, -ah, and -nah. Meanwhile, the Dayak Ketungau Sesat language confix (BDKS) consists of pǝ-ne, kǝ-an, sǝ-ne, and kǝ-ne.